The micrometeorite flux to Earth during the earliest Paleogene reconstructed in the Bottaccione section (Umbrian Apennines), Italy. (26th June 2020) - Boschi, Samuele; Schmitz, Birger; Martin, Ellinor; Terfelt, Fredrik
Abstract: Based on sediment‐dispersed extraterrestrial spinel grains in the Bottaccione limestone section in Italy, we reconstructed the micrometeorite flux to Earth during the early Paleocene. From a total of 843 kg of limestone, 86 extraterrestrial spinel grains (12 grains > 63 μm, and 74 in the 32–63 μm fraction) have been recovered. Our results indicate that the micrometeorite flux was not elevated during the early Paleocene. Ordinary chondrites dominated over achondritic meteorites similar to the recent flux, but H chondrites dominated over L and LL chondrites (69%, 22%, and 9%, respectively). This H‐chondrite dominance is similar to that recorded within an enigmatic 3 He anomaly (70, 27, and 3%) in the Turonian, but different from just before this 3 He anomaly and in the early Cretaceous, where ratios are similar to the recent flux ( 45%, 45%, and 10%). The K‐Ar isotopic ages of recently fallen H chondrites indicate a small impact event on the H‐chondrite parent body 50 to 100 Ma ago. We tentatively suggest that this event is recorded by the Turonian 3 He anomaly, resulting in an H‐chondrite dominance up to the Paleocene. Our sample spanning the 20 cm above the Cretaceous–Paleogene (K–Pg) boundary did not yield any spinel grains related to the K–Pg boundary impactor.